'Highlander Ithimu yezwe lonke!': intersections of Highlanders FC fandom and Ndebele ethnic nationalism in Zimbabwe. Issue 9 (2nd September 2018) - Ncube, Lyton
Abstract: Football is one of the most emotive cultural forms through which people experience and express nationalism. The study demonstrates intersections of Zimbabwean Premier Soccer League (PSL) team – Highlanders FC fandom and Ndebele ethnic nationalism in Zimbabwe. This nationalism challenges state narratives of a 'united Zimbabwe' and advocates for secession of Bulawayo and Matabeleland provinces to form an 'independent Ndebele nation'. Literature on Zimbabwean football has under-theorized its interface with football discourse. The author was an observer as participant in Zimbabwean football stadia for a four-year period observing terrace rituals, especially songs and chants during Highlanders FC matches. In-depth interviews were also conducted with selected fans to get clarity on observed issues. The study concludes that while discussing secession is criminalized and condemned as 'tribalism' in Zimbabwe, Highlanders FC fandom is a critical site where some people express feelings and aspirations towards establishment of a separate 'independent Ndebele nation'.